Cradle-to-gate life cycle assessment of Eucalyptus globulus short rotation plantations in Chile. (15th July 2015) - Morales, Marjorie; Aroca, Germán; Rubilar, Rafael; Acuña, Eduardo; Mola-Yudego, Blas; González-García, Sara
Abstract: Short rotation woody crops appear to be a promising option of biomass for bioethanol production. The traditional short rotation periods for Eucalyptus globulus vary between 8 and 12 years, however intensive forest management practices and genetic improvement have increased the productivity of plantations and reduced the rotation periods up to 5 years. This study aims to assess the potential environmental impacts associated with Chilean short rotation E. globulus plantations for bioenergy production from a Life Cycle Assessment perspective. Thus, for the first time it is presented a detailed life cycle inventory and environmental assessment of a forest system in Latin America. Forest operations carried out over a lifespan of 12 years, with rotation periods of 4 years, were divided into four phases: crop establishment, harvesting, hauling and logistics infrastructure. The managed life cycle inventory included forest site data from a representative plantation dedicated to Eucalyptus chips production for energy purposes, and the inventory of the fuels production in Chile was also determined to fulfil the information requirement. The environmental profile was analysed in terms of several impact categories: climate change, ozone depletion, terrestrial acidification, freshwater y marine eutrophication, photochemical oxidant formation, human toxicity, terrestrial ecotoxicity, freshwater ecotoxicity, marine ecotoxicity, water depletion and fossil fuel depletion. The harvesting phase was the main contributor to almost all the impact categories with contributing ratios higher than 56%. Within the harvesting phase, fertilisation and forwarding were the main processes responsible for derived environmental impacts. The results in terms of climate change and terrestrial acidification were compared with those reported for Eucalyptus biomass production in European countries. The comparison was performed considering the same system boundaries and functional unit. Differences identified were related to different forest management activities carried out as well as different biomass yields. The LCA study remarked those stages where the researchers need to improve the environmental performance. The results suggested that both fertiliser dosage and fuel consumption in forest activities should be optimised in order to decrease most effectively the global environmental impacts. Highlights: LCA of short rotation Eucalyptus globulus for bioenergy production was performed. Real forest information corresponding to Chilean practices was considered. The forest scenario considers a lifespan of 12 years under a short rotation regime. The harvesting phase was the main responsible of environmental impacts. Fertilising and forwarding processes were identified as the environmental hotspots .